Design formulations - ZAKIAN, V. (International journal of control, 1987)
A growing trend in the computer-aided design of classical control systems is to formulate the design problem so that it is soluble by numerical (mathematical programming) methods. This paper derives criteria for assessing the suitability of such formulations, proposes new formulations and discusses the implications of the new formulations for the development of control theory.